A Study of Multi Criteria Decision Analysis of Accident data for Indian states. Issue 1 (June 2021) - Sharma, Pankaj; Jain, J K; Kallaa, Pawan; Kumar, Parveen
Abstract: Traffic accident is a great worry for traffic safety experts and city planners and authorities because it leads to serious and non-serious injuries, loss of human life and some material loss also. The major causes of traffic accidents has been due to interaction of person, motor vehicle, road and situation. It has been observed that in some states or cities or areas traffic accidents occur very frequently as compared to other states or places. By adopting Multi-criteria decision-making (MCDM) techniques, the ranking of various Indian states is carried out based on 11 evaluative criteria. By considering these evaluative criteria, like the fatal accidents, grievous injury accidents, minor injury accidents, severity of road accidents, eleven traffic safety criteria are adopted. In the first stage of the model, these eleven criteria has been given weights as per Entropy Weight Method (EWM). In the second phase, ten Indian States have been ranked based on these eleven criteria by adopting Technique of Order Preference Similarity to the Ideal Solution (TOPSIS) method. The attained results show which of the state is best ranked. Using these eleven criteria, the proposed model evaluates the road safety performance for a given set of 10 Indian states.